2006
DOI: 10.1016/j.shpsb.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Philosophy enters the optics laboratory: Bell's theorem and its first experimental tests (1965–1982)

Abstract: This paper deals with the ways that the issue of completing quantum mechanics was brought into laboratories and became a topic in mainstream quantum optics. It focuses on the period between 1965, when the Bell published what we now call Bell's theorem, and 1982, when Aspect published the results of his experiments. Discussing some of those past contexts and practices, I show that factors in addition to theoretical innovations, experiments, and techniques were necessary for the flourishing of this subject, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 71 publications
0
7
0
12
Order By: Relevance
“…A well documented example of such stifling effects is provided by research into the foundations of quantum mechanics. Freire (2004Freire ( , 2006 reported that in 1960-1980's, despite practical success of quantum theory, research related to basic issues, first raised by Einstein in his disputes with Bohr (exemplified by the famous EPR paper, Einstein et al 1935), was a rather poor choice for scientific career. Even formulation of Bell theorem (Bell 1964) and its extensions (most notably Clauser et al 1969), which provided mathematical rigor to the problem, did little to change this.…”
Section: Discussionmentioning
confidence: 99%
“…A well documented example of such stifling effects is provided by research into the foundations of quantum mechanics. Freire (2004Freire ( , 2006 reported that in 1960-1980's, despite practical success of quantum theory, research related to basic issues, first raised by Einstein in his disputes with Bohr (exemplified by the famous EPR paper, Einstein et al 1935), was a rather poor choice for scientific career. Even formulation of Bell theorem (Bell 1964) and its extensions (most notably Clauser et al 1969), which provided mathematical rigor to the problem, did little to change this.…”
Section: Discussionmentioning
confidence: 99%
“…O trabalho de Bell teve uma repercussão inicial muito discreta, até que um grupo de físicos (John Clauser, Michael Horne, Abner Shimony e Richard Holt) se debruçou sobre este e acabou propondo uma desigualdade derivada desse teorema, conhecida como CHSH (Clauser, Horne, Shimony, & Holt, 1969), que poderia ser testada em laboratórios de óptica quântica (Freire Jr, 2006). As primeiras medições a fim de testar as desigualdades de Bell foram realizadas por Freedman e Clauser a partir de uma transição entre estados de um átomo de cálcio, que resultava na emissão de dois fótons (Freedman, & Clauser, 1972).…”
Section: Apêndice O Emaranhamento Visto Como Um Dos Fundamentos Da Teunclassified
“…Ao propor o estudo do emaranhamento quântico, é necessário tratar a compreensão do fenômeno tomando inicialmente o contexto no qual se deram as reflexões teóricas propostas por Einstein, Podolsky e Rosen (Einstein, Podolsky, & Rosen, 1935) e promover seu reconhecimento como campo de investigação consolidado na Física. Esses fatos se inserem em uma cadeia complexa e repleta de sutilezas, se estendendo entre a metade da década de 30 e a primeira metade da década de 80 (Freire Jr, 2006), produzindo intensos debates até os dias atuais.…”
Section: Introductionunclassified
“…Due mentioning is the essential international resonance that this event have had in the following developments, as Freire noticed: […] the Erice 1976 meeting, which was seen by some physicists as the turning point in the acceptance that quantum nonlocality was indeed a new physical effect. (Freire 2006) Also John Clauser, 22 who had already given important contributions to the FQM (Freedman and Clauser 1972) and at that time was part of the FFG remembered: the sociology of the conference was as interesting as was its physics. The quantum subculture finally had come out of the closet.…”
Section: The Erice School On Fqm Of 1976mentioning
confidence: 99%